2015
DOI: 10.1039/c5ra17459g
|View full text |Cite
|
Sign up to set email alerts
|

Flux growth of patterned LiCoO2 crystal arrays directly on a Pt substrate in molten LiNO3

Abstract: We demonstrate a new way to prepare hollow-structured LiCoO2 crystals directly on a Pt substrate for the first time through a combination of semi-additive electrodeposition of a Co core and subsequent flux growth in molten LiNO3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…S1). Very similar results were observed in our previous reports that describe the formation of hollow-structured LiCoO 2 , LiMn 2 O 4 , and LiNi 0.5 Co 0.2 Mn 0.3 O 2 from the conversion of electrodeposited Co, Mn, and stacked Ni/Co/Mn dots in molten salts at high temperatures, respectively 23,24 . Based on these results, the oxide formation on the Nb substrate could limit the reaction kinetics, since the amount of dissolved oxygen is normally small in the molten salts.…”
Section: Resultssupporting
confidence: 91%
“…S1). Very similar results were observed in our previous reports that describe the formation of hollow-structured LiCoO 2 , LiMn 2 O 4 , and LiNi 0.5 Co 0.2 Mn 0.3 O 2 from the conversion of electrodeposited Co, Mn, and stacked Ni/Co/Mn dots in molten salts at high temperatures, respectively 23,24 . Based on these results, the oxide formation on the Nb substrate could limit the reaction kinetics, since the amount of dissolved oxygen is normally small in the molten salts.…”
Section: Resultssupporting
confidence: 91%
“…The LiNi 0.5 Mn 1.5 O 4− δ crystals used were prepared by the flux growth method171819202122. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Very recently, we proposed the extension of the flux growth concept to create a structure in which high-quality LiCoO 2 crystals were obtained from Co metal in molten LiCl (flux). 29 Specifically, a micro-sized hemispherical Co dot, which was directly deposited onto a Pt substrate using electroplating, reacted with LiNO 3 flux causing the formation of high-quality LiCoO 2 crystals. Time-dependent scanning electron microscopy (SEM) and X-ray diffraction (XRD) analyses suggested that the conversion process kinetics involved different reactions, including low LiCoO 2 phase formation leading to hollow structures based on the Kirkendall effect [30][31][32][33] and, also, rapid growth of LiCoO 2 crystals that promoted anisotropic growth.…”
Section: Introductionmentioning
confidence: 99%